Nyadiri : Tradisi Penyembuhan Melalui Ritual Tolak Bala Pada Masyarakat Dayak Di Kota Palangka Raya - Ni Nyoman Rahmawati; I Made Sadiana; Ade Susana (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
The modernization of life today is not an excuse for some Dayak people in Palangka Raya City to abandon various traditions that have been passed down from generation to generation. One of them is the nyadiri ritual as a ritual of repelling reinforcements which is believed to be able to neutralize various negative influences in humans and can cause suffering (illness). There are three types of self-awareness rituals that are often carried out, namely nupi (dreaming) self-awareness, pregnant self-awareness, and self-awareness due to calamity. There are three stages in carrying out self-isolation for sick people, namely the first stage is carried out at home, the second stage is throwing all negative things out of the house according to dreams that are experienced in waterways, behind the house or graves. The third stage is to return the spirit or offerings to the sick person by placing a behas baruan on the crown of the sick person and then sprinkling holy water as a symbol of generating a positive aura for the sick person so that he will be healthy again soon. The meaning of treatment in the nyadiri ritual can be interpreted from the tools and infrastructure used, such as nyiru, banana leaves, statues of Sadiri, Ketupat Sumbawa, Tantaluh Manuk, Hundus Tanak, and Tampung Tawar, all of which are symbols of self-cleansing from negative influences.